Семантическая эвoлюция белорусских диалектных балтизмов - Станкевич, А. (Kalbotyra, 1990)
The paper discusses the basic types of semantic adaptations of Balticisms in the dialects of Byelorussia – metaphoric and metonymic change, specialization and generalization of meaning leading to polisemy which is a stable index of the complete assimilation of a foreign lexeme in the receiving language.The distinctive feature of the semantic structure of dialectal Balticisms is their complex nature, which depends upon the early date of their borrowing, the extensive area of their functioning and the specific character of the vocabulary of a dialect itself.